Multi-Family Therapy for First Episode Psychosis: Experiences of Families in Singapore - Loh, Christopher; Liang, Wilfred; Lee, Helen; Koh, Astelle (Frontiers in Psychiatry, 2021)
Aim: This qualitative study examined the experiences of families with Multi-Family Therapy (MFT) provided by the Early Psychosis Intervention Programme (EPIP) in Singapore. The MFT was piloted over a period of 2 years and findings from this study were used to further refine the MFT to better meet the needs of Singaporean families in the service. Methods: Families who completed the MFT were invited to participate in the study. Nine clients and ten carers who consented to participate in the study were allocated to two client and two carer Focus Group Discussions (FGDs) respectively. A semi-structured interview schedule was used to facilitate the discussions. The FGDs were audio recorded, transcribed, and anonymised. The data was analysed using thematic analysis. Results: Four main themes emerged from the analysis: (1) therapeutic processes of MFT, (2) positive changes in family relationships, (3) improvements in coping with psychosis, and (4) suggestions for improvement in MFT. The families suggested some structural changes to the MFT, and more carers than clients would prefer therapists to offer more expert advice. Conclusions: Findings suggest that a Western-based MFT can be adapted to work with Singaporean families. This study sheds light on the therapeutic processes that may be related to the changes in family relationships and coping with psychosis. In addition, it suggests that therapists taking an expert and authoritative approach may not fit with the needs of younger generations in Singapore. It advocates for therapists to take a flexible and fluid stance to work with Singaporean families.